PERBEDAAN KEMAMPUAN PEMECAHAN MASALAH DENGAN PENDEKATAN INVESTIGASI DAN PENDEKATAN KONVENSIONAL PADA POKOK BAHASAN TEOREMA PHYTAGORAS DI KELAS VIII SMP NEGERI 9 PEMATANGSIANTAR - Theresia Monika Siahaan (Universitas Islam Sumatera Utara, 2019)
Abstract. This study aims to determine whether there are differences in mathematical problem solving abilities of students who are taught through an investigative approach and with conventional approaches in class VIII SMP 9 of Pematangsiantar. This type of research is experimental research. The population in this study were all eighth grade students of SMP 9 of Pematangsiantar as many as 8 classes. The problem solving abilities of students taught with an investigative approach to the average pretest of 57.73 and post-test of 85.42, the level of change in problem solving abilities was 27.69. Higher than the problem solving abilities of students who are taught with conventional learning the average pretest is 56.67 and posttest is 72.67. Hypothesis testing, from the calculation of student pretest data obtained at dk = 64 and the real level α = 0.05 and ????(1−12∝)=????0,975 obtained ttable = 1.669 and tcount = 1.172. Because tcount ttable = (1.172 1.669) it can be concluded that the initial ability of students is the same. While based on the calculation of student posttest data obtained at dk = 64 and the real level α = 0.05 obtained ttable = 1.669 and t count = 4.212. Because tcount ttable (4.212 1.669) then Ho is rejected and Ha is accepted. Then it was concluded that there were significant differences between problem solving abilities taught by an investigative approach and conventional approaches.Keywords: Problem Solving Ability, Investigative Approach, Conventional Approach.